The future of change how technology shapes social revolutions - Brescia, Ray (Cornell University Press, 2020)
"Explores the connection between social movements, technology, and inequality. It also shows how just as new technologies helped fuel the growth of new movements throughout U.S. history, even newer technologies have emerged in the last decade that are beginning to help groups counter different forms of inequality"--